Cover Image, Volume 84, Issue S1. (19th September 2016) - Moult, John; Fidelis, Krzysztof; Kryshtafovych, Andriy; Schwede, Torsten; Tramontano, Anna
Abstract : Structural superposition of the model T0766TS160_2 (magenta) and CASP11 target T0766 (cyan); The poorly modeled strand‐turn‐strand‐helix motif (residues 52–64) is detected by the accuracy estimator ModFOLD‐single59 (green), with predicted main chain accuracy closely tracking the actual error curve (blue) (red, difference between the estimated and actual error)., DOI:10.1002/prot.25064 .